It's COVID-19 chaos! Is the temporary restriction on short selling in Thailand effective? - Tanakorn Likitapiwat; Sirimon Treepongkaruna (Cogent Economics & Finance, 2022)
This paper evaluates the effectiveness of the COVID-19 temporarily led restriction on short selling by the Stock Exchange of Thailand (SET). We investigate the causal effect of short selling restriction on return, volatility and market quality from 2 September 2019 to 30 September 2020. Exploiting this short selling restriction as a natural experiment, we conduct difference-in-difference analyses and find that the uptick restriction on short selling worsens market quality with higher spread, lower market depth, and order imbalance. In addition, we find an increase in volatility during the restriction and a negative return surrounding the announcement date. This implies that the restriction increases the trading costs and price impact and fails to tame the volatile market and reduce returns.
Keywords: G10; 330; Causal inference; difference-in-difference; market quality; short-selling restriction; Stock Exchange of Thailand